Evaluasi Tingkat Pelayanan Fasilitas Dan Operasional Terminal Penumpang Angkutan Jalan Berdasarkan Peraturan Menteri No. 40 Tahun 2015 Dan SK Dirjend Wahana Tata Nugraha Tahun 2010 - Desi Sartika; Yosi Alwinda; Mardani Sebayang (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The terminal is a road transportation infrastructure that takes the form of a transportation node for the purpose of raising passengers, loading / unloading goods, arranging the arrival and departure of public transport and the place to start and end trips. Simpang Aur Terminal is a type A terminal serving inter-city transportation in the province (AKDP), between inter-provincial cities (AKAP) in the City of Bukittinggi. This condition makes facilities at terminals important, but there are still many lack of terminal facilities at Simpang Aur that have not met Terminal service standards based on PM No. 40 of 2015. Therefore, it is necessary to evaluate Simpang Aur terminal service facility standards to improve terminal services good in accordance with established standards, safe and comfortable for users. The method used in this study is the method of direct observation, literature, and interviews. The results of the Simpang Aur terminal facility service standard analysis based on the availability of available infrastructure, in terms of reliabilit/regularity, obtained a suitability value of 60%, comfort services obtained 36.4% conformity value, and convenience /affordability services that is 80%. The loading factor for AKDP public transportation is 44.58%, and for AKAP is 46.72%. Waiting time / parking duration for AKDP 44 minutes, for AKAP 81 minutes. The results of the analysis of the physical condition based on the Dirjen Wahana Tata Nugraha Decree in 2010 showed that the physical condition of Simpang Aur Terminal was 59% that met the requirements, with the assessment weight in the range ≤60% included in the medium category, then for Terminal Aur facilities needed additional facility as a type A terminal for convenience for terminal infrastructure users.Keywords: Simpang Aur Terminal, Type A Terminal, Terminal Facilities, Physical Conditions, Service Standards.